Evaluation of the RealStar® SARS-CoV-2 RT-PCR kit RUO performances and limit of detection - Visseaux, Benoit (J Clin Virol, 2020)
BACKGROUND: The use of efficient, reliable and sensitive PCR assays is a cornerstone in the race to contain the SARS-CoV-2 pandemic. In this work we performed an independent evaluation of the RealStar® SARS-CoV-2 RT-PCR Kit Researh Use Only (Altona) for SARS-CoV-2 detection. METHODS: A comparative limit of detection (LoD) assessment was performed between RealStar® SARS-CoV-2 and the currently WHO recommended RT-PCR (WHO-PCR) workflow using a quantified clinical sample. Assessment of the RealStar® SARS-CoV-2 assay was also performed using 83 primary clinical samples in comparison with the WHO-PCR. RESULTS: The RealStar® SARS-CoV-2 demonstrated a slightly higher sensitivity than the WHO recommended assay with a limit of detection at 625 copies/mL instead of 1250 copies/mL for the WHO-PCR in our conditions. The overall percent agreement between RealStar® SARS-CoV-2 and WHO-PCR on 83 clinical samples was 97.6 % (81/83) with a sensitivity at 97.8 % (45/46) and specificity at 97.3 % (36/37). No cross reaction was encountered for the other human coronaviruses (HKU1, OC43, NL63, 229E). CONCLUSIONS: In this comparison of the RealStar® SARS-CoV-2 assay with the reference WHO assay, we observed a slightly better sensitivity of the RealStar® assay. It provides a robust option for all molecular biology laboratories, with a strong real-life LoD and is compatible with various real-time PCR platforms.